An energy-efficient two phases cluster head selection in corona-based wireless sensor networks. (2015) - Fan, Chung-Shuo
Owing to unbalanced traffic pattern of wireless sensor networks (WSNs), larger load is imposed to cluster heads (CHs) around the sink. Under this situation, CHs closer to the BS drain their energy earlier than those farther away from the sink. This paper first formulates cluster density of each corona according to the energy consumption of each CH. Then, this paper defines the range of CH candidates in phase 1 and 2 to choose the suitable CH so that sensor nodes forward data towards the BS and reduce the energy consumption. This paper further adopts cluster maintenance, which implement the cross-level data transmissions when specific conditions happen. Simulation results show that the proposed TPS (Two Phases cluster head Selection in WSNs) effectively prolongs the network lifetime and reduces the energy consumption over low energy adaptive clustering hierarchy (LEACH) and multi-hop routing with LEACH (MR-LEACH).